Assessment instrument for integrated information system success in institution of higher learning - Ruzaini, Abdullah Arshah (2012)
Assessing Integrated Information System (IS) in organisations is an important initiative as it would enable Information System (IS) managers and the top management to judge whether or not their investment for IS integration have been successful and worthwhile. Current research on uS assessment is rare and focuses on the assessment of technical aspects of ITS without considering the organisational and strategic aspects. This study tries to establish success factors and criteria of uS which are used as the basis for constructing the instrument to assess uS in an organisation. A list of relevant success factors and criteria for ITS was discovered through literature and was grouped into three main domains of ITS which are technical, organisational and strategic. Manual and online surveys to establish the factors and criteria for uS assessment were conducted among uS experienced practitioners. Factor analysis was carried out to confirm the strength of the factors and criteria within their respective domain groups. Using the factors and criteria compiled from the survey, an instrument for ITS assessment is constructed. Result from factor analysis has established three main technical success criteria which are system quality, timeliness and reliability, and information quality. The result also has established three main organisational success criteria namely organisational impact, user and service satisfaction, and positive usage. Furthermore, it has also established five main success factors which are project management and communication, project quality and culture, management support, project team and technical support, and knowledge and priority. Verification from three institutions has shown that the instrument is reliable and able to provide meaningful representation of uS success status in organisation. The Pearson correlation coefficient value (r) between success factors and criteria are 0.88, 0.57 and 0.88 respectively, which indicates that the identified success factors • have strong influences on the success criteria. These results support that the proposed assessment instrument is able to provide descriptive values as well as the level and factors of success that contributes to the success or failure of an uS. This research contributes to the development of an assessment instrument by incorporating technical, organisational and strategic domains for uS to be used in Institutions of Higher Learning.